Influencer Marketing and TikTok Electronic Word of Mouth: Examining Their Effects on Repurchase Intention with Brand Trust as a Mediator - Ensi Rahmayanti; Rahmadania; Ana Fitriana; Wenny Pebrianti; Bintoro Bagus Purmono (Al-Qalam Institue, 2026)
The rapid growth of social media, particularly TikTok, has transformed how consumers build relationships with brands and develop intentions to repurchase products. This study aims to examine the effects of influencer marketing and electronic word of mouth (eWOM) on repurchase intention, with brand trust acting as a mediating variable. A quantitative research approach was employed using a survey of 200 active TikTok users who had previously purchased or tried products promoted on the platform. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that influencer marketing has a significant effect on both repurchase intention and brand trust. Meanwhile, TikTok eWOM significantly influences brand trust but does not directly affect repurchase intention. Brand trust is found to have a significant effect on repurchase intention and plays an important mediating role in strengthening the relationship between influencer marketing, eWOM, and repurchase intention. These findings highlight the importance of building brand trust to transform digital marketing communication into sustainable consumer loyalty and repeated purchase behavior in social media–driven markets.